Molecular Docking Studies of Nyctanthes arbor-tristis Phytochemicals for Targeting TNF Receptor in Arthritis - Shradha Nagawade (International Journal of Cell Biology and Cellular Functions, 2025)
Rheumatoid Arthritis is an autoimmune disorder which results in inflammation. Tumor necrosis factor-alpha (TNF-α) is responsible for the progression of inflammatory arthritis by promoting immune cell activation and cytokine release. The present study explores the potential of bioactive compounds derived from Nyctanthes arbor-tristis (Parijat) in modulating TNF receptor activity through molecular docking. Computational methods were employed to evaluate the binding affinity of selected phytocompounds from N. arbor-tristis against the extracellular domain of the TNF receptor. Molecular docking was performed using PyRx, and the pharmacokinetic properties of the ligands were analyzed using ADMET filters to assess their drug-like potential. Molecular docking analysis revealed that the ligands Decan-1-ol, 1,3-Distearin, and 2,3,4,6-Tetramethyl-D-Glucose demonstrated the highest binding affinity toward the 1ext protein, indicating their strong potential for receptor interaction. Further in vitro study is needed to confirm their effectiveness.
Keywords: ADMET analysis; Nyctanthes arbor-tristis; Phytochemicals; arthritis; computational screening; molecular docking; tumor necrosis factor receptor